"Qual é a boa?": das categorias de língua às categorias de discurso na construção de identidades de gênero - Lopes, Mônica Aparecida Lima (2009)
This research contemplates an analysis of beer advertising campaigns, which portrait women as element of seduction. The purpose of this study is to broaden the traditional notion pointed in Portuguese Grammars, referring to the language categories that focus on intensification. Among these categories, the main point are adjectives and adverbs. This analysis aims at showing the rhetoric process of woman s transformatio n, from a thematic/figurative point of view - which overcomes the verbal level and explores mainly the visual one in the construction of an aggregated identity with social values and ideology. The theoretical background of research recovers the main concepts of the Semiolinguistics Theory of the Discourse Analysis, by Charaudeau. The notion of ethos, revisited by Maingueneau (2001) and Amossy (2005), is also emphasized. The television pieces Skol, Brahma, Antarctica and Kaiser brands were chosen as they are the industry leaders, according to the Top of Mind research (2007). Thus, the theoretical perspective brings up the problematic of associating discourse to a specific communicative situation, showing that the word people use to communicate their perceptions is not an accurate reflection of the world, but a representation of it. Consequently, the meaning of a term has no value by itself: it only acquires a purpose in a specific social context, which provides social value in language exchange. Therefore, it's fair to admit that the language somehow mirrors the position and the conduct of someone in the society, as well as the way in which each one perceives their role.